EKSPLORASI INOVATIF POTENSI JAMUR ENTOMOPATOGEN (Beuveria bassiana) SEBAGAI BROAD-SPECTRUM BIONSECTICIDE DALAM MENDUKUNG SISTEM PENGENDALIAN HAMA TANAMAN PANGAN YANG RAMAH LINGKUNGAN - Citra Chantyka Muslimah; Angel Areysia Siagian; An-Nisa Fitri Khotia Siregar; Indah Gresia Tampubolon; Syairal Fahmy Dalimunthe (STKIP Subang, 2026)
The excessive use of chemical pesticides can cause various negative impacts, including pesticide residues in food crops, human health problems, environmental pollution, and a decline in biodiversity. Therefore, environmentally friendly and sustainable alternatives for pest control are needed. One promising biological agent is the entomopathogenic fungus Beauveria bassiana. This study aims to review and synthesize previous research findings regarding the potential of Beauveria bassiana as a broad-spectrum bioinsecticide. The study employed a literature review method by collecting and analyzing ten relevant national and international scientific articles. Data were analyzed using a qualitative descriptive approach through the identification, comparison, and synthesis of previous research findings. The results indicate that B. bassiana is effective in controlling various insect pests from several orders, including Hemiptera, Lepidoptera, Coleoptera, and Orthoptera. This capability is supported by its infection mechanism, which includes inoculation, germination, penetration, dissemination, and colonization, as well as the production of extracellular enzymes and secondary metabolites that enhance fungal virulence against insect hosts. In addition, B. bassiana can colonize plant tissues as an endophytic fungus, potentially improving plant growth and resistance. Based on the synthesis of previous studies, Beauveria bassiana has considerable potential to be developed as a broad-spectrum bioinsecticide that is environmentally friendly and supports sustainable agricultural practices.